Inhibition of Amebic Lysosomal Acidification Blocks Amebic Trogocytosis and Cell Killing - Allissia A. Gilmartin (American Society for Microbiology, 2017)
ABSTRACT Entamoeba histolytica ingests fragments of live host cells in a nibbling-like process termed amebic trogocytosis. Amebic trogocytosis is required for cell killing and contributes to tissue invasion, which is a hallmark of invasive amebic colitis. Work done prior to the discovery of amebic trogocytosis showed that acid vesicles are required for amebic cytotoxicity. In the present study, we show that acidified lysosomes are required for amebic trogocytosis and cell killing. Interference with lysosome acidification using ammonium chloride, a weak base, or concanamycin A, a vacuolar H+ ATPase inhibitor, decreased amebic trogocytosis and amebic cytotoxicity. Our data suggest that the inhibitors do not impair the ingestion of an initial fragment but rather block continued trogocytosis and the ingestion of multiple fragments. The acidification inhibitors also decreased phagocytosis, but not fluid-phase endocytosis. These data suggest that amebic lysosomes play a crucial role in amebic trogocytosis, phagocytosis, and cell killing. IMPORTANCE E. histolytica is a protozoan parasite that is prevalent in low-income countries, where it causes potentially fatal diarrhea, dysentery, and liver abscesses. Tissue destruction is a hallmark of invasive E. histolytica infection. The parasite is highly cytotoxic to a wide range of human cells, and parasite cytotoxic activity is likely to drive tissue destruction. E. histolytica is able to kill human cells through amebic trogocytosis. This process also contributes to tissue invasion. Trogocytosis has been observed in other organisms; however, little is known about the mechanism in any system. We show that interference with lysosomal acidification impairs amebic trogocytosis, phagocytosis, and cell killing, indicating that amebic lysosomes are critically important for these processes.